Interplay of manufacturing-induced thermal residual stresses and microvoids in damage and failure of fiber-reinforced composites. (15th March 2023) - He, Jinlong; Cui, Xiaodong; Lua, Jim; Liu, Ling
Highlights: The interplay of manufacturing-induced thermal residue stress and microvoids in the damage progression and failure of fiber-reinforced composites. A micromechanics-based computational framework is employed for mechanical properties. Thermal residue stress has a significant influence on transverse tensile, shearing, and compressive strength. Microscale stress concentration factor can quantify the local stress concentration. The proposed micromechanics-based approach has competitive accuracy in predicting the mechanical performance under various voids, TRS, and loading conditions. Abstract: Fiber-reinforced composites have inherent thermal residual stresses (TRS) and microvoids that are both generated during the manufacturing process. While the two factors are naturally included in experimental measurements as they preexist in the specimens for testing, theoretical and computational modeling of composites usually neglect these two or include only one. Such simplifications inevitably introduce errors to the predicted mechanical properties of composites, which may further influence the reliability of subsequent modeling and design efforts. Using a micromechanics-based failure modeling approach, this work investigates the effects of both TRS and microvoids on the mechanical properties of fiber-reinforced composites. The TRS is generated when composites are cooled down from the curing temperature. The microvoids are assumed to take realistically existing circular, triangular, square, and pentagonal shapes. Damage progression is systematically studied in six representative loading modes, five voids, and two TRS conditions. All results are statistically extracted to account for geometric uncertainties. The study unravels the interplay of TRS and microvoids in determining the mechanical properties of composites along with the corresponding failure mechanisms. This investigation provides high-fidelity predictions and theoretical insights to improve our understanding of TRS and microvoids in composites, mitigate their impacts, and guide future modeling and design efforts. Graphical abstract: Image, graphical abstract